Using LESLLA readers’ miscues to inform pedagogical practice - Gonzalves, Lisa (LESLLA Symposium Proceedings, 2023)
LESLLA practitioners worldwide assist with emergent print literacy development of the L2 adults in their classrooms, yet research on adult emergent literacy, including the stages of emergent reading development in the adult L2 context, is still relatively unexplored. This 12-month study tracked 2 female LESLLA learners who had advanced to a Beginning High ESL class at their school. During weekly literacy intervention sessions, the participants read aloud level-appropriate text without any prior scaffolding, to showcase how they decoded text independently. Leveraging miscue analysis, audiorecordings were transcribed, with miscues further transcribed phonetically (using IPA). Preliminary results showcase nearly a dozen types of miscues, including eliminating/inserting/ transposing/deleting phonemes, articulating semantically-similar or visually-similar words, articulating the wrong word form, confusing voiced/voiceless consonant sounds, and only correctly articulating the first few phonemes. Despite two different L1s, the learners both demonstrated common processing problems. Implications discuss suggestions for classroom instruction for higher-level LESLLA learners.